DEVELOPMENT OF HEALTH INSURANCE MODEL IN HEALTHCARE - qizi , Umurzakova Mutabarkhan Nodir (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY RESEARCH AND INNOVATIVE TECHNOLOGIES, 2021)
This article analyzes the strengths and weaknesses of the existing global health care models and proposals for health care reform in the social protection system of Uzbekistan.